KEMAMPUAN BACILLUS LICHENIFORMIS DALAM MEMPRODUKSI ENZIM PROTEASE YANG BERSIFAT ALKALIN DAN TERMOFILIK - Soeka, Yati Sudaryati; Rahayu, Sri Hartin; Setianingrum, Ninu; Naiola, Elidar (Badan Penelitian dan Pengembangan Kesehatan, 2011)
The aim of the research was to measure the production of protease enzyme in alkaline and thermophilic of bacteria Bacillus licheniformis. The protease enzyme signed by clear zone arround the bacteria colonies on medium which contain 1% skimmed milk. The activities of protease enzyme treated by the period of incubation, temperature and pH, which measured by spectrophotometer at ? 280 nm. The results showed that the highest production of protease activity at 2 days incubation was 150,52 U/mL. At temperature 50°C and pH 10 they were 123,34 U/mL and 193,14 U/mL.